Bioestimulantes em oliveira, do viveiro ao campo: jardim clonal, produção de mudas e óleo essencial - Ritter, Giovana (2022)
The growth of national olive cultivation increases the demand for seedling production and the residue of this production can add value. The objective of the present work was to evaluate the growth of olive seedlings in a nursery and the performance of a clonal garden in the field with the use and application of biostimulants, as well as to evaluate the yield of essential oil extracted from the leaves. In this sense, four experiments were carried out, the first two with seedlings, the third with a clonal garden and the fourth with essential oil extraction. In experiment I, the seedlings received treatments with Azospirillum brasilense and humic substances, at concentrations of 0.4 and 0.5 mL per plant. In experiment II, the same product as in experiment I was applied, in different modes of application (foliar spraying, via soil and immersion), at a concentration of 0.5 mL per plant. Applications were performed monthly, as well as phytotechnical assessments of height (cm), neck diameter (mm) and number of nodes. At the end of 210 days, after the first application, 15 plants were selected per treatment for evaluation of fresh and dry biomass of the shoot and root. Experiment III referred to the clonal garden, being implemented in September 2019, with one-year-old seedlings of the cultivars Ascolano 315, Maria da Fé, Koroneiki and Picual, in a spacing of 0.50 x 1.0 m. After planting, the plants were pruned at a height of 50 cm. The treatments were applied monthly to the rhizosphere: T1 - control, T2 - 0.5 mL of A. brasilense, T3 - 0.4 mL of humic substances and T4 - humic substances + A. brasilense. The evaluations took place monthly for two years, as height (cm), accumulated growth rate (cm day-1), neck diameter (mm) and mean internode length (cm). At the end of the first year, evaluations of total plant biomass (kg), length of the largest branch (m), cutting yield and fresh and dry leaf biomass (g). At the end of the second year, total plant biomass (kg), length of the largest branch (m) and cuttings yield. The experimental design used was randomized blocks, in a 3 x 4 factorial scheme (cultivars x biostimulants), with 4 repetitions and 5 seedlings per repetition (experiment I) and a 3 x 4 factorial (cultivars x application modes of A. brasilense), with 3 repetitions and 5 seedlings per repetition (experiment II), both with split plot in time. In experiment III, the experimental design used was randomized blocks, in a 4 x 4 factorial scheme, with 3 repetitions and 3 plants per repetition, subdivided in time and essential oil extraction performed in triplicate by repetitions. Seedlings of the cultivar Maria da Fé obtained greater growth with the use of the sprayed biostimulant. For the Ascolano 315 cultivar, the use of biostimulants was not recommended. The immersion of the roots of the cultivar Arbequina in the biostimulant was efficient in the development of the root system. The method of application by immersion was not efficient in the formation of seedlings of the three cultivars studied. Humic substances favored agronomic attributes. The cultivar Maria da Fé showed the highest yield of cuttings. The cultivars Maria da Fé and Koroneiki were more vigorous.